HUBUNGAN PIJAT BAYI DENGAN PERKEMBANGAN MOTORIK PADA BAYI USIA 3-12 BULAN DI AINARA MOM AND BABY SPA MARGOYOSO PATI: The Relationship Between Infant Massage And Motor Development In Babies Aged 3-12 Months At Ainara Mom And Baby Spa Margoyoso Pati - Sika, Ira Maya (LPPM - STIKES Pemkab Jombang, 2023)
Infant massage can be classified as a touch application, because in infant massage there are elements of touch in the form of affection, attention, sound or speech, eye sight, movement, and massage. This stimulation will stimulate the development of the structure and function of brain cells. This study aims to determine whether there is a relationship between infant massage and motor development in infants aged 3-12 months at Ainara Mom and Baby Spa Margoyoso Pati. This type of research is an analytic survey. The population in the study were 35 babies aged 3-12 months at Ainara Mom and Baby Spa Margoyoso Pati. As for the sampling technique using total sampling. The sample in this study were 35 respondents. It can be concluded that there is a relationship between baby massage and the motor development of babies aged 3-12 months at Ainara Baby SPA Margoyoso Pati (p value 0.000 > 0.05)